(3JbQjQ Yf GdecJHI GdYGeI HGdQHGWs - (3YHO Gddg GdQLQGLjs
(3ChdgG (B:s
(3hJaJM GdecJHI ddYehe WjdI GdSfI cdgG s
(3BNQgG (B:s
(3hdfNJe gfG gPg GdYLGdI hcJGH NeSI hNOeI KdGKI s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B- (3GdQHGW (B(D 1127) s
Keywords: (3Gdabg GdMfajs